Pengaruh Likuiditas, Kebijakan Hutang, dan Aktivitas terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Yanuarta, Ramel; Sari, Shinta Permata (Jurnal Kajian Manajemen Bisnis, 2013)
This study to examine the effect of liquidity (current ratio/CR), debt policy (debt ratio/DR), and activity (total asset turnover/TATO) on profitability (return on equity/ROE) at the manufacturing companies listed in the Indonesia Stock Exchange (IDX). This study considered causal comparative study, the study population is a manufacturing company listed on the Stock Exchange from 2007 until 2010. Based on purposive sampling method obtained 224 samples. The type of data used are secondary data. Data obtained from www.idx.co.id. The method of analysis used is multiple regression analysis. The research proves that (1) current ratio has positive and unsignificant effect on ROE, (2) debt ratio has negative and unsignificant effect on ROE, (3) total asset turnover has positive and significant effect on ROE. Thus, the major determinant of the profitability of a company is the total asset turnover, for which the company manufactures and investors should pay attention to these variables.